Pengaruh Gaya Mengajar Guru Pendidikan Agama Kristen dan Budi Pekerti terhadap Motivasi Belajar Siswa Kelas XI di SMA N 1 Siborongborong Tahun Ajaran 2024/2025 Kabupaten Tapanuli Utara - Maria Betauli Manurung; Sudirman Lase; Damayanti Nababan; Senida Harefa; Gracetinovitria Butar-butar (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this research is to determine the influence of the teaching style of Christian Religious Education and Character Education teachers on the learning motivation of class Xl students at SMA Negeri 1 Siborong-borong, North Tapanuli Regency for the 2024/2025 academic year. The method used in this research uses quantitative descriptive inferential research methods. The population was all students who were Protestant Christians in class Data was collected using a positive closed questionnaire with 35 items. The results of data analysis show that there is an influence of the teaching style of Christian Religious Education and Character Education teachers on the learning motivation of class rxy value = 0.494 > rtable(a=0.05,n=50) = 0.279, thus it is known that there is a positive relationship between variable .05,dk=n-2=48)= 2.021, thus there is a significant relationship between variable .81X. b) Regression coefficient of determination test (r2) = 24.4%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=15, dk denominator=n-2=50-2=48) namely 15.45 > 1.92. Thus, Ha, that is, there is an influence of the teaching style of Christian Religious Education and Character Education teachers on the learning motivation of class.